Pengembangan Soal Tes menggunakan Aplikasi Quizizz pada Mata Pelajaran Dasar Teknik Ketenagalistrikan - Tommi Setrial Danif; Usmeldi Usmeldi (Jurnal Pendidikan Teknik Elektro, 2026)
Conventional learning evaluation methods such as using paper are considered less valid, less reliable, and impractical. The solution offered is the development of test questions using the Quiizizz application in the Basic Electrical Engineering subject that is valid, reliable, and practical in SMK. The method used is the Research and Development ADDIE model (Analyze, Design, Development, Implementation, Evaluation). Research data was obtained through questionnaires distributed to research respondents, namely class X students of Electrical Engineering at SMK Negeri 1 Pariaman. To produce research products, namely valid, reliable, and practical test questions, validation was carried out by two expert lecturers in their fields. The product was tested for validity using the Aiken's V formula. The results of the test questions' validity can be categorized as valid. The reliability test used the Kuder Ricadson 20 formula. The results of the test questions' reliability can be categorized as reliable. The practicality test showed results that were included in the practical category.